Trans-Metode Dakwah dan Karya-Karya Kiai Bisri Musthofa dalam Penyiaran Islam di Pulau Jawa - Saepudin (Prodi Ilmu al-Qur'an dan Tafsir, 2020)
The method of da'wah as an important instrument in religious broadcasting must experience continuous development, in line with the speed of science and the level of human intelligence, as well as social conditions. The Trans-Method discourse of preaching will researchers juxtapose with one of the charismatic figures of the 19th century AD from the 60 - 90s period on the island of Java, namely Kiai Bisri Musthofa. This figure is quite antique compared to other religious figures of his period. He is a multi-talented figure in religious, social, cultural and political aspects. Its influence in the development of Islam on the island of Java, especially in the area of ??Rembang and its surroundings is very high. His intelligence in responding to social, cultural, religious and political issues has been tested. This truth can be seen from his works which can be categorized in the fields of interpretation, hadith, aqidah, sharia, morals / tasawuf, language, culture and others. The theme in this paper will focus on how to fully describe the strategy of da'wah kiai Bisri Musthofa through various methods of broadcasting Islam in the Java region.